Legal substratum and social conditions of dissolution of marriage in Moldavia: comparative study (14th–17th centuries) - Zabolotnaia, Lilia (Balcanica Posnaniensia. Acta et studia, 2022)
The main objective of the study is to show the specifics and features of the social phenomenon of divorce in medieval Moldavia. Divorce was known in all civilizations, however, in the context of European history, both common and specific features were observed in the Principality of Moldavia. The study of documentary historical, legal and act material of the era, notes and information of Catholic missionaries shows that in the Principality of Moldavia not only men, but also women had the right to divorce and remarry. Moldavian women could and had the right to initiate a divorce.